Analysis of Interleukin 8 (IL-8) Levels, Blood Urea Nitrogen/Albumin Ratio, Pneumonia Severity Index, and Length of Stay in Patients Undergoing Pulmonary Rehabilitation and Shortwave Diathermy - Cindy Carrissa Primaputri; Yani Jane R. Sugiri; Iin Noor Chozin; Aditya Sri Listyoko; Yunita Eka Wati; Rahmad Rahmad (Medicinski glasnik, 2025)
Objective: This study aims to analyze the effects of Pulmonary Rehabilitation (PR) and short-wave Diathermy (SWD) on the Blood Urea Nitrogen (BUN)/Albumin ratio, Pneumonia Severity Index (PSI), IL-8 levels, and length of stay (LOS) in hospitalized pneumonia patients. Material: and method: This is a randomized experimental study with a pre-post control group structure. The study included 24 pneumonia patients who were treated at Dr. Saiful Anwar General Hospital and Lawang General Hospital between 2022 and 2023. For 5 days, subjects were separated into three groups: control, intervention (PR only), and intervention (PR and SWD). The data were examined by comparing the deltas of each group. PSI and CURB-65 were used to calculate severity indices and blood samples were obtained before and after the intervention to determine the BUN/Albumin ratio and IL-8 levels. Results: There was a significant decrease in the BUN/Albumin ratio after the intervention (p=0.03). IL-8 levels and LOS showed a decreasing trend, although not statistically significant (p=0.208; p=0.249). There was a substantial correlation between PSI and IL-8 and the BUN/Albumin ratio (p=0.015; p=0.002; p=0.001). Conclusion: This study highlights reduced IL-8 levels, the BUN/Albumin ratio, and a shorter LOS in pneumonia patients receiving PR and SWD therapy for 5 days. This study reinforces the evidence that PR and SWD can serve as adjunctive therapies for patients with pneumonia.
Keywords: BUN/Albumin ratio; pneumonia; interleukin-8 (IL-8); pulmonary rehabilitation; and shortwave diathermy.